Analisis Penetapan Tingkat Marjin Akad Pembiayaan Murabahah: Studi Kasus pada Baitul Maal wa Tamwil Ahmad Yani Malang - Putra, Baskoro Perdana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Determination of the margin level of murabaha financing contract should not refers to the prevailing interest rate. This research has a purpose to know how to or model of determine the margin level of murabaha financing contract at Baitul Maal wa Tamwil Ahmad Yani Malang. This research uses descriptive qualitative research method with a case study approach. This case study research focuses on Baitul Maal wa Tamwil Ahmad Yani Malang. The result of this research is that the determination of the margin level of murabaha financing contract in BMT Ahmad Yani Malang does not refer directly to the prevailing interest rate. BMT Ahmad Yani Malang has a margin level determination method that is based on the level of profit-sharing ratio, the average margin level market, the rate of profit to be obtained, and other costs. Keywords: margin level, murabahah, benchmark interest rates